Tennis Elbow and its Homoeopathic Management (Homoeopathy for All, 2022)
Tennis elbow is the painful condition  that occurs due to over burden of  elbow tendons. It is also known as  Lateral epicondylitis. People who do  not play tennis can also suffer from  this condition. In fact only 5 % of  people who plays tennis suffering  from it.1 Apart from the tennis  players, it is seen in carpenters,  painters, and plumbers. It is usually  presented with pain and tenderness  around the common extensor origin  of the elbow. If we look back, Runge2 in 1873 was the first who described  about Tennis Elbow and Henry  Morris3 eventually gave its name  ‘Lawn Tennis Arm’ in his writing in  the Lancet. 1-3% of adult population  is estimated to suffer from Tennis  elbow each year. Tennis elbow is 7  times more common than golfers  elbow (medial epicondylitis).4 It is  caused by repeated micro trauma  and failure of the healing process  in the soft tissue attachments of  the extensor carpi radialis brevis,  origin of occupational or sporting  activities. Prevalence of tennis  elbow is identified in patients  from 12 to 80 years of age. Age  group between 30 - 60 years is  19% prone for the development of  tennis elbow.5 Steroidal and non steroidal anti-inflammatory drugs  (NSAIDs) along with physiotherapy  is considered in the conventional  treatment. NSAIDs are having  harmful effects on vital organs. It  has been reported clinically that such  injuries are not completely healed  by such measures. Homoeopathic  medicines can be beneficial to speed  up the recovery. In this article, we  will briefly go through the literature  on efficacy of homoeopathy in sports  injuries along with its therapeutic  indication.
Keywords: therapeutic; Tennis elbow; painful